Commercial determinants of youth smoking in ASEAN countries: A narrative review of research investigating the influence of tobacco advertising, promotion, and sponsorship - Thomas Stubbs (Tobacco Induced Diseases, 2021)
Introduction Tobacco smoking is one of the leading causes of death and disability in the Association of Southeast Asian Nations (ASEAN). Despite implementation of some tobacco control measures, youth continue to initiate smoking. This narrative review outlines how tobacco advertising, promotion, and sponsorship (TAPS) may influence smoking attitudes and uptake among youth in the region.